PENGUBURAN MASA LALU PADA MASYARAKAT SUPIORI DI KABUPATEN SUPIORI - Maryone, Rini (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
Death got more attention, in the event of death the funeral ceremony will be performed. In a ceremony tailored to the age and social status of the deceased. The funeral procession comes armed with the grave and the bodies of the dead pet. Form of burial was found at the site in Kampung Pasir Panapasyem Bamboo Supiori Eastern District, is a type of burial in the cave / recess in the form of burial types of primary (direct) without a container.